Fabrication of a γ-In2Se3/Si heterostructure phototransistor for heart rate detection. Issue 25 (22nd June 2021) - Zhang, Yue; Wang, Ming; Cao, Kaijun; Wu, Chunyan; Xie, Chao; Zhou, Yuxue; Luo, Linbao
Abstract : A γ-In2 Se3 /Si heterostructure phototransistor presents a high responsivity arising from the photogating effect. It shows potential applications in real-time and accurate health monitoring, such as heart rate detection. Abstract : A γ-In2 Se3 /Si heterostructure phototransistor with a broadened photoresponse has been developed, presenting a responsivity, specific detectivity and response speed of 10.24 A W −1, 8.63 × 10 12 Jones and 0.76/0.85 ms (rise time/fall time) at 450 nm, respectively. The high responsivity could be attributed to the depressed dark current of the γ-In2 Se3 nanofilm and the high gain arising from the gating effect of the phototransistor. Further analysis reveals that the relatively high responsivity and fast response speed facilitate the application of the device in real-time and accurate health monitoring, such as heart rate detection.